User-Centric Solutions for Scholarly Research in the Library - Sadeh, Tamar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
In recent years, the behavior of library users has been undergoing change, as they rely increasingly on web search engines and internet services, rather than libraries, to fulfill their information needs. This paper describes the expectations of such users when looking for information and presents an optimized approach that enables research libraries to provide their patrons with an up-to-date user experience while capitalizing on the unique advantages offered by libraries. Ways of integrating the new solution with the current library environment are discussed, as well as future directions. The Primo discovery and delivery system from Ex Libris serves as an example of such solutions.